2011
DOI: 10.1007/s10596-011-9244-4
|View full text |Cite
|
Sign up to set email alerts
|

Open-source MATLAB implementation of consistent discretisations on complex grids

Abstract: Accurate geological modelling of features such as faults, fractures or erosion requires grids that are flexible with respect to geometry. Such grids generally contain polyhedral cells and complex grid-cell connectivities. The grid representation for polyhedral grids in turn affects the efficient implementation of numerical methods for subsurface flow simulations. It is well known that conventional two-point flux-approximation methods are only consistent for K-orthogonal grids and will, therefore, not converge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
191
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(197 citation statements)
references
References 26 publications
0
191
0
Order By: Relevance
“…The initial control values were chosen as the average of the upper and lower bounds. The whole exercise was performed in the open-source reservoir simulator MRST Lie et al [15], by modifying the adjoint-based optimization module to allow for robust optimization and combining it with the EnKF …”
Section: D Five-spot Modelmentioning
confidence: 99%
“…The initial control values were chosen as the average of the upper and lower bounds. The whole exercise was performed in the open-source reservoir simulator MRST Lie et al [15], by modifying the adjoint-based optimization module to allow for robust optimization and combining it with the EnKF …”
Section: D Five-spot Modelmentioning
confidence: 99%
“…Some such models have recently been implemented using the CO 2 module of the open-source MATLAB Reservoir Simulation Toolbox (Lie et al 2012;MRST 2014;SINTEF ICT 2014), as demonstrated in several recent publications (Andersen et al 2014;Nilsen et al 2014a, b, c).…”
Section: Other Simplifying Assumptionsmentioning
confidence: 99%
“…The implementation of the mixed MsFEM is based on the code of Aarnes. For further details we refer to [5,18].…”
Section: Acknowledgmentmentioning
confidence: 99%